2009
DOI: 10.1007/s11244-009-9421-z
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Vegetable Oils into Hydrocarbons over CoMo/MCM-41 Catalysts

Abstract: Deoxygenation of triglycerides over Co and Mo sulfides supported on a series of mesoporous molecular sieves (MCM-41) with varying Si/Al ratio has been investigated in this contribution. The catalysts were tested in a flow reactor at reaction temperatures 300 and 320°C, hydrogen pressures 2-11 MPa and space velocities 1-4 h -1 using refined rapeseed oil as a feedstock. Incorporation of Al into the framework of MCM-41 led to an increase of both conversion of triglycerides and selectivity to hydrocarbons, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 22 publications
3
49
0
1
Order By: Relevance
“…Under identical reaction conditions (280-310°C) an increase in overall hydrogen pressure (from 0.7 to 7 MPa) suppressed hydrodecarboxylation of triglycerides at the expense of their hydrodeoxygenation [10,67]. On the other hand, increasing reaction temperature (from 280 to 310°C) promoted hydrodecarboxylation over hydrodeoxygenation at constant pressure (7 MPa) [10,17,18].…”
Section: Supported Metal Sulfides Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under identical reaction conditions (280-310°C) an increase in overall hydrogen pressure (from 0.7 to 7 MPa) suppressed hydrodecarboxylation of triglycerides at the expense of their hydrodeoxygenation [10,67]. On the other hand, increasing reaction temperature (from 280 to 310°C) promoted hydrodecarboxylation over hydrodeoxygenation at constant pressure (7 MPa) [10,17,18].…”
Section: Supported Metal Sulfides Catalystsmentioning
confidence: 99%
“…The activity of hydrotreating catalysts is affected by the nature of the support and its properties [57]. Several efforts to understand the role of support on the activity and selectivity metal sulfides catalysts used for deoxygenation of triglycerides were reported [67,74]. Specifically, mesoporous materials have shown great potential as catalyst supports [75,76] and have been reported to provide some advantages over conventional alumina support in hydrotreating applications [77,78].…”
Section: Supported Metal Sulfides Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies that have investigated the thermal conversion (pyrolysis and cracking) of triglycerides for obtaining hydrocarbon fuels (Alencar et al 1983;Ali and Hanna 1994;Dandik and Aksoy 1998;1999;Gusmao et al 1989;Kubicka et al 2010;Lima et al 2004;Maher and Bressler 2007;Schwab Simacek et al 2009). Results showed that conversions ranged between 54 and 100 % and were heavily dependent on operating variables.…”
Section: Gasoline and Diesel Range Hydrocarbons From Waste Vegetable mentioning
confidence: 99%
“…These catalysts consist of Co-and Nipromoted MoS 2 supported on γ-alumina. HDO of vegetable oil feedstock using supported NiMo sulfides has been studied in the past [4,9,23,8,[24][25][26][27][28][29][30][31][32]. Usually, model compounds have been employed in this context [25][26][27][28]33,34].…”
Section: Introductionmentioning
confidence: 99%